A comparison between the open-ended coaxial probe method and the parallel plate method for measuring the dielectric properties of low-moisture foods. (August 2020) - Lau, Soon Kiat; Dag, Damla; Ozturk, Samet; Kong, Fanbin; Subbiah, Jeyamkondan
Abstract: The dielectric properties of reference materials (deionized water and heptane) and selected low-moisture foods (ground black pepper, all-purpose bleached wheat flour, non-fat milk powder, and whole milk powder) were measured with the open-ended coaxial probe (OECP) and parallel plate (PP) methods from 20 to 60 °C and in the frequency ranges of 5 MHz to 3 GHz for OECP and 5–30 MHz for PP. Overall, the PP method was more accurate at measuring the dielectric properties of the reference materials than the OECP method. Notably, the OECP deviated from expected values below 200 MHz or when the magnitudes of the dielectric properties were small. As for the food products, the OECP and PP data sets were interpolated well with a modified power law model at lower temperatures when the OECP data below 200 MHz were excluded. However, the OECP data largely deviated from PP data at higher temperatures. The results suggest that the PP method may be preferable if the frequencies of interest are below 200 MHz or if the dielectric properties are expected to be small in magnitude. Highlights: Two method of measuring dielectric properties of low-moisture foods were compared. Parallel plate is better for radio frequencies and low dielectric properties. Open-ended coaxial probe does not work well with small dielectric property values. Open-ended coaxial probe is more suitable for microwave frequencies.